유아음악교육에서의 음원 사용에 관한 연구 - 이소현(So-Hyun Lee); 모아라(A-Ra Mo) (디지털콘텐츠학회논문지, 2017)
본 연구의 목적은 유아음악교육에서 음원 사용의 실태, 디지털 음원 사용에 관한 사용 방법, 장점 및 이유, 단점 등을 파악하는데 있다. 연구대상은 유아음악교육에 관심을 가지고 활동에 참여하는 유아교사 8명으로 포커스 그룹 인터뷰를 통해 자료를 수집하였다. 연구 결과, [음원 사용 실태]는 <디지털 음원이 자주 사용됨>, <상황에 따라 직접 연주도 필요함>으로, [사용방법]은 <유료로 다운로드 후 카세트로 제공>, <노트북, 스마트폰으로 제공>으로, [사용 장점 및 사용 이유]는 <사용하기 편리함>, <연주하기 어려운 곡의 경우 요긴함>으로 [음원 사용 단점]은 <다양하지 못함>, <사용방법이 불편할 때도 있음>으로 주제가 분류되었다. The purpose of this study is to identify the use of sound sources in music education for children, discuss how to use the digital sound sources, and explain the advantages and the disadvantages. The study participants collected data through focal group interviews with 8 preschool teachers interested in music education for children. The results of the study are as follows. Actual use of sound sources were divided into two categories: "Digital sound source is frequently used," "Need to play directly according to circumstances." The method of digital sound source use was divided into "Download as paid and provided as a cassette," "Playing sound sources directly from laptops and smartphones." Benefits and reasons for digital sound source use was divided into "Easy to use," and "Necessary when it is difficult to play the actual piece." Demerits of digital sound source use was divided into "Lacking variety" "Inconvenience of use." This study is believed to be meaningful in providing the basis for the provision of sound sources in music education for children and the basic sources of research on the use of sound sources. KCI Citation Count: 3